1997
DOI: 10.1111/j.1346-8138.1997.tb02778.x
|View full text |Cite
|
Sign up to set email alerts
|

Hormonal Profiles and Prevalence of Polycystic Ovary Syndrome in Women with Acne

Abstract: One of the important etiologic factors in acne is an increase in sebaceous gland activity, which is androgen dependent. Acne is a common manifestation of hyperandrogenemia. Therefore, acne may not only cause cosmetic concern but may also be a sign of underlying disease. In females, the most common cause of hyperandrogenemia is polycystic ovary syndrome (PCOS). The purpose of this study was to determine the hormonal profiles of women with acne and the prevalence of PCOS in women attending the dermatological cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
56
1
5

Year Published

2001
2001
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(69 citation statements)
references
References 19 publications
7
56
1
5
Order By: Relevance
“…20 Timpatanapong P et al studied hormonal profiles and prevalence of polycystic ovary syndrome in women with acne in1997 and documented frequent association of acne in women with PCOS. 21 83.75% of patients in this study had acne which is similar to the results obtained by Timpatanapong P et al 21 85% patients in the present test group had lost weight at the end of 6 months while only 55% in the control group had lost weight in 6 months. Weight loss of more than 5% was considered significant.…”
Section: Discussionsupporting
confidence: 88%
“…20 Timpatanapong P et al studied hormonal profiles and prevalence of polycystic ovary syndrome in women with acne in1997 and documented frequent association of acne in women with PCOS. 21 83.75% of patients in this study had acne which is similar to the results obtained by Timpatanapong P et al 21 85% patients in the present test group had lost weight at the end of 6 months while only 55% in the control group had lost weight in 6 months. Weight loss of more than 5% was considered significant.…”
Section: Discussionsupporting
confidence: 88%
“…BMI had weak positive correlation with serum prolactin, serum cholesterol, fasting blood sugar, fasting insulin and insulin resistance ( . However, in two other studies mean age was found 25.6±3.9 and 27±5 years respectively [12][13] . In this series 16 cases were of above 30 years which is comparable to the findings of Sangabathula et al 14 .…”
Section: Resultsmentioning
confidence: 99%
“…The role of androgens in the pathogenesis of acne vulgaris is well known; elevated androgen levels in women with acne have been confirmed in many studies (5)(6)(7)(8)(9)(10)(11)(12)(13). Androgens elevate sebum production and follicular ceratosis, which plays a major role in the etiology of acne (14).…”
Section: Introductionmentioning
confidence: 92%